Translation problems of fantasy literature : A case study of The Southern Vampire Mysteries, True Blood and The Fever series - Palin, Sofi (My University, 2020)
This thesis discusses fantasy fiction and the specific problems related to translating it. The problems are approached from the perspective of the translator, looking at both real translations and originals that are yet to be translated. A successful fantasy work immerses the reader into the fictional fantasy world and keeps their interest throughout the story. Some of the strategies that strive for this outcome cause problems for the translators of fantasy fiction. One of the strategies to make the fictional world more credible for the readers is to make the world very intricate. The intricateness of fantasy worlds is maintained by, among other things, different names, expressions, swearwords, titles, altered meanings of words, new words coined by the author and fictional culture bound concepts. These can become problematic for translators, because these concepts may not work within the rules of the normal world and some of the concepts may not have counterparts in reality. The first part of the thesis examines fantasy fiction as a literary genre and introduces different definitions and divisions of fantasy. In the second part of the thesis, the translation problems related to fantasy fiction are discussed in more detail through examples. The examples have been gathered from two contemporary novel series, the (as yet untranslated) Fever Series by Karen Marie Moning and the Southern Vampire Mysteries by Charlaine Harris. Part of the material is from a TV series, True Blood, based on the Southern Vampire Mysteries. True Blood and the Southern Vampire Mysteries have been translated into Finnish and these translations are compared with each other. The thesis illustrates that it is important to pay attention to the details that create depth to the story. A translator should have in-depth knowledge of the genre and some personal interest towards it in order to be successful at translating it. It was demonstrated that two fantasy series, that look superficially similar, might not be so similar from the perspective of translation as the authors may use significantly different strategies in executing their fictional worlds.
Keywords: translation, fantasy fiction, urban fantasy, high fantasy, low fantasy, fictional world, names, irrealia, altered meanings